EFFECT OF ULTRAVIOLET RADIATION ON THE FORMATION OF ERGOCALCIFEROL (VITAMIN D2) IN Pleurotus ostreatus - Ruslan, K -; Reza, R.A -; Damayanti, S. - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2011)
Naturally the content of ergocalciferol (vitamin D2) in mushrooms is small, but they are rich of ergosterol which is known as its precursor. Ergosterol converted to vitamin D2 by UV light irradiation following by heat reaction. The aim of the study is to observe formation of ergocalciferol from its precursor in the Pleurotus ostreatus using UV radiation at 254 and 366 nm. Crude samples were irradiated for 15, 30, 60, 90, and 120 minutes. The samples were then extracted using reflux for one hour. Ergocalciferol content was determined using spectrophotodensitometer. The results show that the content of ergocalciferol after 15, 30, 60, 90, 120 mins radiation under UV 254 nm are 24.12 ± 3.46; 28.15 ± 1.43; 38.22 ± 2.11; 48.19 ± 3.68; and 14.81 ± 3.41 μg/g respectively, whereas under UV 366 nm in similar duration the content are 9.59 ± 5.35; 20.6 ± 5.58; 27.67 ± 4.5; 10.62 ± 2.81; 8.76 ± 0.32 μg/g, respectively. No ergocalciferol is found in the control. It is concluded that the ergocalciferol was formed in mushroom after irradiating with ultraviolet light. The highest ergocalciferol content was found in sample irradiated under UV light 254 nm for 90 minutes.Keywords: Ergocalciferol, ergosterol, duration, irradiated, Pleurotus ostreatus spectrophotodensitometer, ultraviolet light